The Ex-Date Wealth Effect of Rights Offerings in the Philippines - Ybanez, Roy C. (Philippine Management Review; Vol 5 (1994), 2016)
Rights offerings in the Philippines in the period January 1987 – March 1995 show significant market adjusted returns averaging 7.6% on ex-date.  The excess returns are not driven by outliers, the sectoral mix of the offerings, nor by the large representation of 1994 offerings.  We surmise that the excess returns represent a liquidity premium and hence, reflect a normalization of prices on ex-date.  The prospects of illiquidity and a significant increase in investments in the stock could put downward pressure on stock prices (possibly soon after the announcement of the offering).  We find a high correlation between excess returns and the proportion of capital rendered illiquid.  The sample consists of 42 offerings by 28 companies with transactions for each of the 10 days surrounding the ex-date, out of a total 110 offerings by 63 listed companies during this period.